Burnout and use of HIV services among health care workers in Lusaka District, Zambia: a cross-sectional study - Quiterio Nicole; Nkhoma Mavis; Ikeda Scott; Chapula Bushimbwa; Kruse Gina R; Pankratz Debra; Mataka Kaluba; Chi Benjamin H; Bond Virginia; Reid Stewart E (BMC, 2009)
Abstract Background Well-documented shortages of health care workers in sub-Saharan Africa are exacerbated by the increased human resource demands of rapidly expanding HIV care and treatment programmes. The successful continuation of existing programmes is threatened by health care worker burnout and HIV-related illness. Methods From March to June 2007, we studied occupational burnout and utilization of HIV services among health providers in the Lusaka public health sector. Providers from 13 public clinics were given a 36-item, self-administered questionnaire and invited for focus group discussions and key-informant interviews. Results Some 483 active clinical staff completed the questionnaire (84% response rate), 50 staff participated in six focus groups, and four individuals gave interviews. Focus group participants described burnout as feeling overworked, stressed and tired. In the survey, 51% reported occupational burnout. Risk factors were having another job (RR 1.4 95% CI 1.2-1.6) and knowing a co-worker who left in the last year (RR 1.6 95% CI 1.3-2.2). Reasons for co-worker attrition included: better pay (40%), feeling overworked or stressed (21%), moving away (16%), death (8%) and illness (5%). When asked about HIV testing, 370 of 456 (81%) reported having tested; 240 (50%) tested in the last year. In contrast, discussion groups perceived low testing rates. Both discussion groups and survey respondents identified confidentiality as the prime reason for not undergoing HIV testing. Conclusion In Lusaka primary care clinics, overwork, illness and death were common reasons for attrition. Programmes to improve access, acceptability and confidentiality of health care services for clinical providers and to reduce workplace stress could substantially affect workforce stability.